Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pcbi.1006769
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Structure in Micro-ECoG Recordings is Described by Spatially Coherent Components

Abstract: Electrocorticography (ECoG) is becoming more prevalent due to improvements in fabrication and recording technology as well as its ease of implantation compared to intracortical electrophysiology, larger cortical coverage, and potential advantages for use in long term chronic implantation. Given the flexibility in the design of ECoG grids, which is only increasing, it remains an open question what geometry of the electrodes is optimal for an application. Conductive polymer, PEDOT:PSS, coated microelectrodes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Moreover, the channel correlation was systematically reduced in awake compared to anesthetized mice, reflecting the asynchronous network activity in awake states. In a recent study, channel correlations performed in mice and humans could resolve local activity patterns even when ECoG recording sites were less than 1 mm apart (Rogers et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the channel correlation was systematically reduced in awake compared to anesthetized mice, reflecting the asynchronous network activity in awake states. In a recent study, channel correlations performed in mice and humans could resolve local activity patterns even when ECoG recording sites were less than 1 mm apart (Rogers et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that the low and high-frequency oscillations of ECoG are associated with different spatial correlation levels. Recently, Rogers et al (2019) showed that the correlation between recording contacts of ECoG electrodes drops quickly for high frequencies after 2-3 mm, but takes longer to drop for lower frequencies. In our earlier work, we recorded ECoG during resting and movement execution with electrodes having 1.2 mm contact size and 4 mm spacing (Jiang et al, 2015).…”
Section: Spatial Profile Of Hfb-ers and Lfb-erdmentioning
confidence: 99%
“…Therefore, as a second approach, we regressed out electrode distance dependencies from FC values. Given the fact that volume conduction is dependent on electrode distance (Dubey and Ray, 2019;Rogers et al, 2019;Rouse et al, 2016), this approach is expected to substantially dampen possible volume conduction effects. Specifically, we fit cubic spline curves to the mean of the FC values within each nonoverlapping 1 cm range of electrode distance.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%